(untitled) (Bangladesh Journal of Agricultural Research, 2015)
A pot experiment was carried out in the net house of Soil Science Division of Bangladesh Agricultural Research Institute (BARI), Joydebpur Gazipur on 16 March 2010 and 12 January 2011 with a view of study the effect of P addition to As-contaminated soils and the consequences on As uptake of maize (Zea mays L.) plants. Experiments were conducted in consecutive two years. Arsenic was added to the pots at the rates of 0, 20 and 30 mg kg?1, and P at 0, 30 and 60 mg kg?1. Thus there were seven treatment combinations, i.e., As0P0, As20P0, As30P0, As20P30, As20P60, As30P30, and As30P60. Phosphorus fertilization increased total As uptake, but the increase was restricted to the root. As concentration of root was much higher than that of shoot. As concentrations in shoot and root were positively correlated (r = 0.913, r = 0.975; P<0.01) in 2010 and 2011, respectively, and plant As was positively correlated to the plant P in shoot (r = 0.883 and 0.875; P<0.01) and in root (r = 0.829, P<0.05 and 0.917; P<0.01). The plants took up much greater amounts of P than As. Although it is well known that phosphate inhibits arsenate uptake (Wang et al., 2002), but it is highlighted the role of P fertilization to increase As uptake in maize plants. The results presented here indicate P supply may effect in higher As allocation to the plant parts, which has practical application in soil-crop systems. These findings could have important implications for human health and agricultural systems, since it may reduce As contamination through the consumption of crops (phytoextraction) grown on contaminated soils. Bangladesh J. Agril. Res. 40(2): 217-227, June 2015